Identifikasi larva nyamuk di Kelurahan Bulu Cendea Kabupaten Pangkep - Rahmadana, Nurul; Ka’bah; Sulfiani (Program Studi Teknologi Laboratorium Medis, 2024)
Mosquitoes are abundant in nature almost everywhere and are detrimental to human life. This research aims to determine the types of mosquito larvae in Bulu Cendea Village, Pangkep Regency. This research was carried out by collecting mosquito larvae in 17 residential houses. Collection of larvae in water reservoirs in houses and yards in Bulu Cendea Village, Pangkep Regency. Furthermore, observations were made in the DIII Medical Laboratory Technology tropical infections laboratory in July 2019. The results of the research showed that from 17 residential houses in Bulu Cendea Village, Pangkep Regency, there were 110 Aedes agepty larvae, 94 Culex, 9 Anopheles, 2 Mansonia. The total number of mosquito larvae present in Bulu Cindea District, Pangkep Regency, there were 215 larvae.